About “Paleozoic roots” of the oils of the eastern Ciscaucasia - N. Sh. Yandarbiev; R. F. Sachsenhofer; A. N. Stepanov; D. N. Yandarbieva (Georesursy, 2024)
The paper considers geochemical data on the biomarker composition of oils from the fields of the TerekCaspian oil and gas basin. Samples of oils from the fields of the main oil and gas bearing regions of the Eastern Ciscaucasia – Terek-Sunzha zone, Prikumsky swell, Piedmont Dagestan and the Middle Caspian Sea were studied. To determine the “geochemical” age of oils, the ratios of regular steranes in saturated oil fractions were analyzed. It was found that the value of the biomarker parameter St28/St29, which determines the geological age of the original organic matter for oils, varies widely – 0.36–1.47. The most “ancient” age (Devonian-Carboniferous) was determined for the oils of the Prikumsky swell and the water area of the Middle Caspian; in the Terek-Sunzha zone and Piedmont Dagestan, an increase in the proportion of St28 sterane is recorded in oils, which indicates a younger generation age (up to the Paleogene). The data obtained can be used to clarify the history of the formation of hydrocarbon accumulations in this region.